Influence of early life status epilepticus on the developmental expression profile of the GluA2 subunit of AMPA receptors - Szczurowska, E; Ergang, P; Kubová, H; Druga, R; Salaj, M; Mareš, P (Experimental neurology, 2016)
AMPA receptors (AMPARs) are responsible for fast excitatory neurotransmission, and their prolonged activation can result in the generation and spread of epileptic seizures. At early stages of postnatal development, the majority of AMPARs are permeable to both Na(+) and Ca(2+) ions. This permeability, which increases neuronal excitability, is due to the lack of the GluA2 subunit, encoded by the GRIA2A gene, and/or the presence of an unedited GluA2 subunit Q/R site (glutamine instead of arginine). Lithium chloride- and pilocarpine-induced status epilepticus (LiCl/Pilo-SE) in rodents represents a model of severe seizures that result in development of temporal lobe epilepsy (TLE). The aim of this study was to determine how LiCl/Pilo-SE induced early in life (at postnatal day 12; P12) alters normal expression of the GRIA2A gene and GluA2 protein. SE was interrupted by an injection of paraldehyde (Para). Control groups were 1) naïve animals, and 2) siblings of SE rats receiving only LiCl and paraldehyde (LiCl/Para). The expression profile of GRIA2A mRNA was determined via qPCR, and GluA2 protein levels were measured by western blotting. The analysis was performed at 3h (protein levels), and then 3-, 6-, 13-, and 60days, following LiCl/Pilo-SE or LiCl/Para injection (i.e. at P12, P15, P18, P25, P72 respectively). Six different brain regions were analyzed: frontal (CXFR), parietal (CXPAR), and occipital (CXOC) cortex, dorsal (HD) and ventral (HV) hippocampus, and thalamus (TH). There was a significant increase in GRIA2A mRNA expression in the CXFR, CXPAR, and CXOC of P18 SE animals. In CXFR and HD, increased expression of GluA2 AMPAR subunit protein was detected, as well as a surge in GRIA2A mRNA and GluA2 protein expression especially at P18. In HD the surge was detected not only during development (P18), but also later in life (P72). Since high levels of GluA2 can be neuroprotective (by decreasing Ca(2+) permeability), our data suggest that the neocortex and dorsal hippocampus are able to activate endogenous antiepileptic mechanisms. A marked decrease in the overall expression of GluA2 protein in the HV in the LiCl/Pilo-SE and LiCl/Para rats, suggests that the HV is predisposed to excitotoxicity, not only during development, but even in adulthood. Interestingly, LiCl in combination with paraldehyde can also strongly alter the normal ontogeny of GRIA2A mRNA as well as GluA2 subunit protein expression.
Keywords: Disease Models, Animal; novorozená zvířata; AMPA receptory; vývojová regulace genové exprese; věkové faktory; Pilocarpine; RNA, Messenger; Lithium Chloride; pilokarpin; zvířata; messenger RNA; Fluoresceins; Rats; Status Epilepticus; status epilepticus; mužské pohlaví; modely nemocí na zvířatech; Receptors, AMPA; Convulsants; Brain; mozek; krysa rodu Rattus; fluoresceiny; konvulziva; Rats, Wistar; Animals; Male; chlorid lithný; Animals, Newborn; Gene Expression Regulation, Developmental; Age Factors; potkani Wistar